2004
DOI: 10.1002/jsfa.1943
|View full text |Cite
|
Sign up to set email alerts
|

Fish protein hydrolysates from gold carp (Carassius auratus): I. A study of hydrolysis parameters using response surface methodology

Abstract: The combined effects of pH, temperature (T), substrate/buffer ratio (S:B) and enzyme concentration (E) on protein recovery from gold carp (Carassius auratus) processing waste with Flavourzyme  were characterised. The effect of hydrolysis parameters on the degree of hydrolysis (DH) was described through response surface analysis (RSA) and the model obtained was defined as follows: DH = −316.30+ 7.1T + 44.5pH + 0.292S:B + 0.27E − 0.048T 2 − 2.407pH 2 − 0.002S:B 2 − 0.307TxpH − 0.002S:BxE. All regression coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…The results showed that Alcalase 2.4 L exhibited a relatively high degree of hydrolysis (%DH) and high protein recoveries (unpublished results). Similar findings for high protein recoveries and %DH in Alcalase‐assisted reactions have been reported with sardine (Quaglia and Orban 1987a), dogfish muscle (Diniz and Martin 1996), gold carp filleting by‐products (Sumaya‐Martinez et al. 2005), yellowfin tuna (Guerard et al.…”
Section: Introductionsupporting
confidence: 81%
“…The results showed that Alcalase 2.4 L exhibited a relatively high degree of hydrolysis (%DH) and high protein recoveries (unpublished results). Similar findings for high protein recoveries and %DH in Alcalase‐assisted reactions have been reported with sardine (Quaglia and Orban 1987a), dogfish muscle (Diniz and Martin 1996), gold carp filleting by‐products (Sumaya‐Martinez et al. 2005), yellowfin tuna (Guerard et al.…”
Section: Introductionsupporting
confidence: 81%
“…While the contrary has been demonstrated in previous studies,25, 26, 36 this is surely due to the fact that our chosen temperature area is not wide enough and centred around the high enzyme activity temperature area (Protamex has an optimal temperature range of 31–55 °C). Other studies have also shown, with experimental design procedure, that temperature did not possess a significant effect on hydrolysis (DH) when the temperature corresponded to the enzyme temperature range 37, 38…”
Section: Discussionmentioning
confidence: 96%
“…It has been successfully applied to optimize processing conditions, for example, to study the effect of pH, temperature (T) and enzyme-substrate (E/S) ratio on the degree of hydrolysis, the recovery of nitrogen or the protein yield [21][22][23][24]. RSM defines the effect of the independent variables, alone or in combinations, on the process and generates a mathematical model that accurately describes the overall process [21].…”
Section: Introductionmentioning
confidence: 99%